Comparison study of several underwater light scattering phase functions - 黄有为 刘广荣 金伟其 丁琨 李海兰 曹峰梅 王霞 (Optoelectronics letters, 2012)
Scattering phase function is assumed to be one of the most significant factors in the inherent optical properties （lOPs） of natural water. According to three criteria proposed for assessment, several commonly used empirical phase functions are compared with their related practical or theoretical scattering distributions in terms of fitting errors under the circumstances of typical seawater and single-component polydisperse systems. The optimal factors corresponding to the minimum fitting errors are also calculated. It is found that both the one-term Henyey-Greenstein （OTHG） and two-term Henyey-Greenstein （TTHG） phase functions agree well with the theoretical ones for small particles, while the Fouriner-Forand （FF） phase function can be used in the case of suspensions with large suspended particles. The fitting accuracy of OTHG is the worst, FF is better and TTHG is the best.